Management, information systems and technologies in health care : analysis of current status in hospitals of Eastern Slovakia - Gavurová, Beáta, 1972-; Šoltés, Marek, 1974- (Târgu Mureş : Petru Maior University of Târgu Mureş, 2012)
Scientific monograph presents analysis of management of health care organizations and utilization of information systems and technologies in different areas of their activities. Universal methodology of analysis and definition of strategic objectives and values is described.
Bibliogr. odkazy
Resumé
Skratky
Keywords: riadenie nemocnice -- štatistika a číselné údaje; systémy informačné -- štatistika a číselné údaje; technológia -- štatistika a číselné údaje; poskytovanie zdravotnej starostlivosti -- organizácia a riadenie -- sily pracovné -- štatistika a číselné údaje; nemocnice; personál zdravotnícky; plánovanie zdravotnícke; výskum; šírenie inovácií; internet; telemedicína; správanie spotrebiteľa; manažment odpadov; Slovensko; Slovensko východné